Education and masculinities : social, cultural, and global transformations - Haywood, Chris (Christian), 1970-; Mac an Ghaill, Mairtin (London ; Routledge, 2013)
'Across media, academy and popular culture in western societies there is much talk of an implosion of the modern gender order. Education is often presented as a key site in which a crisis of masculinity is played out, and schools have become a focus for practical attempts to reconcile social and cultural transformations through the recalibration of teaching and learning, increasing male teachers and masculinising the content of subjects. This book argues that we are experiencing a shift from the establishment of the social constitution of gender associated with modernity politics, to the gendering of society that has an intensified resonance among men and women in a global-based late modernity. The book explores the main social and cultural approaches to education and masculinities within the broader context of sex and gender relations, considering the masculinity question alongside local and global changes in society, and bringing a fresh evaluation of key issues. Included in the book: - how the suggestion of'academically successful girls' and'failing boys' plays out in relation to issues of inequality - a current empirical analyses of gender inequality across schools, higher education and the labour market - representation, identity and cultural difference with reference to social experiences and cultural meanings - forms of power connected to social divisions and cultural differences. This book provides a critical yet constructive diagnosis of gender relations across educational sites, exploring both academic accounts and alternative global responses that illustrate the limits of Western models and sensibilities.It will be valuable reading for students following courses in education, sociology, gender studies, and other social sciences and humanities courses'--
Social organisation of masculinities : modern schooling, reproduction and resistance -- Schooling, masculinity and class analysis : a new cultural condition in a post-colonial society -- Mediated masculinities in the news : violence, failing boys and sex -- Masculinities across borders : neo-liberalism, militarism and sexual health -- Feminisation, remasculinisation and female masculinity -- Thinking through masculinity : towards a post-masculinity theory in educational contexts.
Includes bibliographical references (p. 130-154).
Keywords: Sex differences in education; Boys -- Education; Masculinity